An experimental investigation on thermal conductivity and viscosity of graphene doped CNTs /TiO2 nanofluid - Zetty Akhtar, Abd Malek; M. M., Rahman; K., Kadirgama; Maleque, M. A. (Universiti Malaysia Pahang, 2020)
This paper presents the findings of the stability, thermal conductivity and viscosity of CNTs (doped with 10 wt% graphene)- TiO2 hybrid nanofluids under various concentrations. While the usage of cutting fluid in machining operation is necessary for removing the heat generated at the cutting zone, the excessive use of it could lead to environmental and health issue to the operators. Therefore, the minimum quantity lubrication (MQL) to replace the conventional flooding was introduced. The MQL method minimises the usage of cutting fluid as a step to achieve a cleaner environment and sustainable machining. However, the low thermal conductivity of the base fluid in the MQL system caused the insufficient removal of heat generated in the cutting zone. Addition of nanoparticles to the base fluid was then introduced to enhance the performance of cutting fluids. The ethylene glycol used as the base fluid, titanium dioxide (TiO2) and carbon nanotubes (CNTs) nanoparticle mixed to produce nanofluids with concentrations of 0.02 to 0.1 wt.% with an interval of 0.02 wt%. The mixing ratio of TiO2: CNTs was 90:10 and ratio of SDBS (surfactant): CNTs was 10:1. The stability of nanofluid checked using observation method and zeta potential analysis. The thermal conductivity and viscosity of suspension were measured at a temperature range between 30˚C to 70˚C (with increment of 10˚C) to determine the relationship between concentration and temperature on nanofluid’s thermal physical properties. Based on the results obtained, zeta potential value for nanofluid range from -50 to -70 mV indicates a good stability of the suspension. Thermal conductivity of nanofluid increases as an increase of temperature and enhancement ratio is within the range of 1.51 to 4.53 compared to the base fluid. Meanwhile, the viscosity of nanofluid shows decrements with an increase of the temperature remarks significant advantage in pumping power. The developed nanofluid in this study found to be stable with enhanced thermal conductivity and decrease in viscosity, which at once make it possible to be use as nanolubricant in machining operation.